Avaliação do estado de conservação da vegetação nas encostas da Serra do Mar - Município de Cubatão, utilizando sensoriamento remoto e SIG - Afonso, Cintia Maria; Bitencourt, Marisa Dantas (Paisagem e Ambiente, 1998)
The city of Cubatão, in the state of São Paulo, comprises significant industrial activities, mainly metallurgy of iron and steel, chemical and petrochemical. It is located in the littoral plain, at the bottom of the "Serra do Mar" mountain range, unabfing the dispersion of the pollutants released daily in the atmosphere by all the industries. The amount of pollution was such in the early 80s that it caused severe damage to the vegetation, specially those located on the mountain slope. As a result, hund reds of soil sliding occurred, strongly affecting the lan dscape. At that time, the state government, through Cetesb, began a program to control industrial pollution in the municipality, which included sowing , "Mata Atlântica" native species over the degraded areas. The purpose of the present study is to verify the vegetation state of conservation after the sow ing program , using remote sensing and GIS techniques.